Naphthalene-based polyimide electrolytes for lithium-ion battery applications - KAYAMAN APOHAN, NİLHAN (WILEY, 2018)
The preparation of 2,6-Bis(m-amino phenoxy) benzoyl naphthalene-based polyimides for solid polymer electrolytes was reported. Li-salt and PEO bearing polyimide membranes were prepared. Thermo-gravimetric analysis results reveal that the PI/PEO/LiCF3SO3 polymer electrolyte membranes are thermally stable up to 500 degrees C. The T-g values are in the range 167-221.5 degrees C according to dynamic mechanical analysis (DMA). The conductivities of Li-salt and PEO containing PI membranes are in the range of 10(-7)-10(-5)S/cm. The conductivity increases with incorporation of PEO and Li+ concentration. The linear sweep voltammetry experiments showed that no peaks were observed between 1.75 and 4.5V.
Keywords: impedance spectroscopy; Li batteries; polyimides; solid polymer electrolytes; POLYMER ELECTROLYTES; MEMBRANES; ELECTRODES; ETHER